Pengaruh Kemandirian Keuangan Daerah Dan Investasi Terhadap Pertumbuhan Ekonomi Dan IPM Di Kawasan Metropolitan Sarbagita - Wardani, Putu Ratih Oka; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2019)
One goals on Sustainable Development Goals (SDG’s) is Public Welfare. In 2009 Bali Province launched a program SARBAGITA metropolitan area. In the SARBAGITA area, economic growth from year to year are fluctuated and has not in line with the development of people's welfare that causing inequality in every SARBAGITA area. Inequality in SARBAGITA area can be a problem in realizing the SARBAGITA area as a metropolitan area. The reserch objective to be analyze the effect of regional financial independence and investment on economic growth, analyze the influence of regional financial independence, investment, economic growth on the welfare and analyze the influence of regional financial independence and investment through economic growth on the welfare of the community in the SARBAGITA metropolitan area. The analysis technique uses path analysis and the results of research on regional financial independence have a significant negative effect on economic growth while investment has a significant positive effect. The independence of regional finance and investment have no a direct effect on public welfare, while economic growth has a significant positive effect. Independence of regional finance and investment has an indirect effect on people's welfare through economic growth.   Keywords : economic growth, community welfare, regional  finance, investastion